UNSUR-UNSUR KESENIAN JAWA DALAM INKULTURASI GEREJA KATOLIK KEVIKEPAN DAERAH ISTIMEWA YOGYAKARTA PERSPEKTIF AKSIOLOGI - , Sukatmi Susantina; , Prof. Dr. Lasiyo, M.A, M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objects of this research consist of two kinds which are object of material and object of formal. The material object stands for arts, specifically a concentrated Javanese arts inculturation while another formal subject is known as axiology or value philosophy. This value begins with a heavy argument between Alexius Meinong, who insisted that feeling is purely the source of value, and Christian van Ehrenfels, who on the other hand claimed that desire, is merely the source of value itself. As it continues, the objective or subjective source of value has been taken into a long discussion for those philosophers. Later on, in daily life, axiology has always long been occurring in many related fields such as education, law, and culture To be clear inculturation is defined as a religion process rooting in any specified arts which admits, adopts, and utilizes it in the act of devotion. Now that the process of inculturation involves the concepts and understanding of axiology interpreted by philosophers, the values of Javanese arts as well as the dimension of axiology, this determined research begins with some literature studies functioning as a framework to sharpen an advanced analysis whenever the field work is conducted. Additionally, the research scope of kevikepan in Jogjakarta is divided into some sub regions where the data analysis is conducted into hermeneutic interpretation, historical comparison and heuristically analysis. Some results obtained from the dissertation furthermore can be concluded as follows